2016
DOI: 10.1016/j.cell.2015.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Heterogeneity in Human Lung Tumors

Abstract: SUMMARY Non-small cell lung cancer (NSCLC) is heterogeneous in the genetic and environmental parameters that influence cell metabolism in culture. Here, we assessed the impact of these factors on human NSCLC metabolism in vivo using intra-operative 13C-glucose infusions in nine NSCLC patients to compare metabolism between tumors and benign lung. While enhanced glycolysis and glucose oxidation were common among these tumors, we observed evidence for oxidation of multiple nutrients in each of them, including lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

44
891
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 911 publications
(939 citation statements)
references
References 33 publications
44
891
3
1
Order By: Relevance
“…However, a recent study by Davidson et al showed that Ras-driven, non-small-cell lung tumors are far less affected by glutaminase inhibition by the GLS inhibitor CB-839, or by CRISPR/Cas-9 based genetic silencing of GLS, than tumor-derived cell lines grown in culture [102]. The authors concluded that tumor microenvironment was responsible for reduced glutamine dependence in whole tumors relative to cultured cells, consistent with a separate report that lung cancer metabolism varies greatly with microenvironment [103]. Although Davidson et al addressed GLS activity, TCGA data suggest that in most lung cancers, GLS and GLS2 are both expressed.…”
supporting
confidence: 72%
“…However, a recent study by Davidson et al showed that Ras-driven, non-small-cell lung tumors are far less affected by glutaminase inhibition by the GLS inhibitor CB-839, or by CRISPR/Cas-9 based genetic silencing of GLS, than tumor-derived cell lines grown in culture [102]. The authors concluded that tumor microenvironment was responsible for reduced glutamine dependence in whole tumors relative to cultured cells, consistent with a separate report that lung cancer metabolism varies greatly with microenvironment [103]. Although Davidson et al addressed GLS activity, TCGA data suggest that in most lung cancers, GLS and GLS2 are both expressed.…”
supporting
confidence: 72%
“…Similarly, 13 C labeling was higher in mouse orthotopic human GBM tumors following injection of [ 13 C]Glc compared with [ 13 C]Gln, suggesting that these tumors use less Gln in vivo (53). Tumors resected following [ 13 C 6 ]Glc infusion produce [ 13 C 3 ]citrate, -malate, and -aspartate, which is consistent with active PC, suggesting that both routes of anaplerosis are utilized by tumors depending on nutrient availability (30,37,46). These studies also suggest that metabolic alterations occur during adaptation to cell culture and/or that the tumor microenvironment substantially influences tumor metabolism (53).…”
Section: Sirm Profiling Of Cancer Systems Can Reveal Novel Metabolic supporting
confidence: 56%
“…To this end, multiple cancer biological models have been used in SIRM studies, including 2D and 3D cell culture, animal tumor models derived spontaneously from defined oncogenic lesions or from implanted tissue/cells, and human tumors analyzed in vivo or ex vivo following surgical resection (35). Regardless of the model, most tumors and derived cells profiled by SIRM recapitulate Warburg's original findings and disprove the canard that tumor cells necessarily have dysfunctional mitochondria (36) by demonstrating that Glc-derived 13 C incorporation into the Krebs cycle can be enhanced in cancerous versus paired non-cancerous tissues (37)(38)(39). Thus, SIRM profiling is excellently suited for uncovering novel aspects of cancer metabolism in model systems and directly in human subjects.…”
Section: Sirm Profiling Of Cancer Systems Can Reveal Novel Metabolic mentioning
confidence: 76%
“…As an illustrative example of the metabolic complexity of tumors, lung cancer cell lines are often glutamine dependent in vitro, but a recent study of K-RAS driven mouse lung tumors demonstrated that glucose but not glutamine was preferentially used to supply carbon to the TCA cycle, through the action of pyruvate carboxylase 190 . Furthermore, two recent metabolomics and metabolic flux studies of primary human lung cancer showed little change in glutamine entry into the TCA cycle, and instead suggested that human lung cancer can synthesize glutamine from the TCA cycle 120,191 . Human and mouse gliomas exhibit high rates of glucose catabolism and accumulate but do not avidly metabolize glutamine 168 , and do not depend on circulating glutamine to maintain cancer growth, but instead utilize glucose to synthesize glutamine through glutamine synthetase to support nucleotide biosynthesis [169][170][171] .…”
Section: Glutamine Usage: Plastic Versus Patientmentioning
confidence: 99%